Regional Geography of Glacier Mass Balance Variability Over Seven Decades 1946–2015 - Braithwaite, Roger J.; Hughes, Philip D. (Frontiers in Earth Science, 2020)
Despite much progress with remote sensing, on–site measurements of glacier mass balance (with stakes and snow pits) still have advantages for resolution of interannual and seasonal changes of mass balance. Understanding these changes may help to identify the types of glaciers most sensitive to climate change. The standard deviation of mass balance data series for a few years describes the interannual variability, and balance amplitude, defined as half the difference between winter and summer balances, describes the seasonal variability. Interannual variability increases with seasonal variability, and seasonal variability increases with annual precipitation and summer temperature available from a half–degree gridded climatology. Measured glaciers have higher mean and median precipitation than average for all glaciers in the Randolph Glacier Inventory (version 6). High balance amplitudes are associated with warm/wet (maritime) environments and low amplitudes with cold/dry (continental) environments, as shown in previous studies of climate at the equilibrium line altitude. Balance amplitude can be modelled for half–degree grid squares in the glacier inventory using multiple regression of measured balance amplitude on the climate data. The resulting modelled balance amplitude is relatively low for Arctic Islands and Central Asia, but high for Western North America, Iceland, Scandinavia, Alps and Caucasus.